The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.17485/ijst/v14i1.1705
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical analysis on anisotropic Bianchi Type-III inflationary string Cosmological models in Lyra geometry

Abstract: Objectives: To present a new solution to the field equations obtained for Bianchi type-III universe by using the law of variation of H, which yields constant DP. Methods: We study a Bianchi type-III cosmological model with a cloud strings with particles connected to them in Lyra geometry. To find the exact solutions of survival field equations we consider here that the shear scalar and scalar expansion are proportional to each other (σ αθ ) that leads to the equation b = c m and secondly we adopt the assumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…R. K. Tiwari et al analysed Bianchi type III string cosmological model in f (R, T) modified theory of gravity by assuming 𝑓 (𝑅, 𝑇) = 𝑅 + 2𝑓(𝑇) which concluded with a note that the universe is in accelerating phase of expansion [2] . Jiten B et al studied Bianchi type-III cosmological model with a cloud string with particles connected to them in Lyra geometry and concluded that the present model starts at 𝑡 = 0 with zero volume and as time progresses it expands with accelerated rate and the model shows that the present universe is particle dominated [3] . Kandelkar et.…”
Section: Introductionmentioning
confidence: 99%
“…R. K. Tiwari et al analysed Bianchi type III string cosmological model in f (R, T) modified theory of gravity by assuming 𝑓 (𝑅, 𝑇) = 𝑅 + 2𝑓(𝑇) which concluded with a note that the universe is in accelerating phase of expansion [2] . Jiten B et al studied Bianchi type-III cosmological model with a cloud string with particles connected to them in Lyra geometry and concluded that the present model starts at 𝑡 = 0 with zero volume and as time progresses it expands with accelerated rate and the model shows that the present universe is particle dominated [3] . Kandelkar et.…”
Section: Introductionmentioning
confidence: 99%
“…Kaiser (Kaiser and Stebbins, 1984), Banerjee (Banerjee et al, 1990), Wang (Wang, 2005), Bali et al (Bali et al, 2007), Power and Deshmukh (Pawar and Deshmukh, 2010), Sahoo and Mishra (Sahoo and Mishra, 2015), Singh (Singh, 2013), Goswami (Goswami et al, 2016), Reddy (Reddy and Naidu, 2007), Khadekar (Khadekar et al, 2005;Khadekar and Tade, 2007), Yadav (Yadav et al, 2011), Ladke (Ladke, 2014), Singh and Baro (Singh and Baro, 2020), Baro and Singh (Baro and Singh, 2020) are some of the authors who studied different string cosmological models within the general relativity in a different contexts in various space-times. In addition to the above mentioned authors, recently Choudhury (Choudhury, 2017), Tripathi (Tripathi et al, 2017), Dubey et al (Dubey et al, 2018), Tiwari et al (Tiwari et al, 2019), Ram et al (Ram and Verma, 2019), Mollah et al (Mollah et al, 2019), and Baro et al(Baro et al, 2021) investigated different string cosmological models in various space times.…”
Section: Introductionmentioning
confidence: 99%
“…A new class of LRS Bianchi type-V cosmological model with string dust as a source of gravitational field was investigated in (12) . In (13) the authors have endeavored to introduce another solution for the field equations obtained for Bianchi type-III cosmological model in Lyra manifold by utilizing the law of variation of Hubble's Parameter (H), which yields constant DP.…”
Section: Introductionmentioning
confidence: 99%